Empowering networking research and experimentation through Software-Defined Networking. (July 2016) - Anan, Muhammad; Al-Fuqaha, Ala; Nasser, Nidal; Mu, Ting-Yu; Bustam, Husnain
Abstract: Software-Defined Networking (SDN) is an evolving network architecture influenced by the increasing popularity in the deployment of Network Virtualization, cloud computing technologies, and the network ossification trend. It represents a new approach to managing, defining and building networks in order to fulfill the needs of the dynamic nature of present day's networking capabilities. In recent years, SDN has emerged as an exciting area of research challenging the current networking paradigm of designing and managing computer networks. SDN represents an extraordinary opportunity to rethink computer networks, enabling the design and deployment of a future Internet. This paper reviews SDN technologies, architectures, applications, underlying protocols, and deployments. It provides taxonomy of recent research works on SDN and highlights some recent practical experiments, with the goal of inspiring new applications and improving the future networking capabilities.